Ese otro Ortiz: Juan L. en revista Claridad - Alzari, Agustín (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2009)
Published in number 205 of Claridad magazine, in April 1930 -an unknown fact to this day-, the three found poems serve as a starting point for a new reading of Ortiz's poetic production, understood as a conscious intervention in the artistic field of the Argentinian lefts in the thirties and forties. Like a bow drawn by the decade, a criticism of his fourth book written in the same magazine in 1941 establishes the suspicion which the 'fighting elegy' arouses, as well as the high standing position occupied by Ortiz within his generation